Effectiveness of acupuncture in polycystic ovary syndrome: A systematic review and meta-analysis of randomized controlled trials. Issue 22 (29th May 2020) - Wu, Jielei; Chen, Di; Liu, Nenghui
Abstract: Objective: To evaluate the effectiveness of acupuncture in reproductive-age females with polycystic ovary syndrome (PCOS). Methods: We searched the Pubmed, Web of Science, Embase, Cochrane, China National Knowledge Infrastructure (CNKI), Wanfang Data, and Chongqing VIP databases for the relevant literature. The meta-analysis was performed with a random-effects model with RevMan 5.3. The primary outcomes of interest included the rate of live birth, pregnancy and ovulation, and the secondary outcomes included the recovery of menstrual period and hormone levels. Results were expressed as the relative risk (RR) for the discrete data and the mean difference (MD) for the continuous outcomes with a 95% confidence interval (CI). Results: Twenty two studies with 2315 participants were included in this systematic review and meta-analysis. A pooled analysis showed a recovery of the menstrual period (5 trials; 364 participants; SMD, −0.52; 95% CI [−0.89, −0.14]; I 2 = 67%; P = .0007; low certainty) in the acupuncture group. Furthermore, there were significant decreases in the luteinizing hormone (LH) (13 trials; 917 participants; MD, −0.92; 95% CI [−1.43, −0.41]; I 2 = 60%; P = .0004; very low certainty) and testosterone (13 trials; 923 participants; SMD, −0.46; 95% CI [−0.73, −0.20]; I 2 = 75%; P = .0006; very low certainty) in the acupuncture group. No significant differences were observed in the rates of live birth, pregnancy, and ovulation, and no significant differences were observed in the LH/follicle-stimulating hormone (FSH) ratio. Conclusions: There was insufficient evidence to support that acupuncture could promote live birth, pregnancy, and ovulation. However, acupuncture could promote the recovery of menstrual cycles as well as downregulate the levels of LH and testosterone in patients with PCOS. Study registration: PROSPERO CRD42019128574. Abstract : Supplemental Digital Content is available in the text